Formal finance usage and innovative SMEs: Evidence from Asean countries - Muhammad Arif; Mudassar Hasan; Ahmed Shafique Joyo; Christopher Gan; Sazali Abidin (Journal of Risk and Financial Management, 2020)
This paper provides evidence on the likelihood of formal finance usage among innovative small and medium enterprises (SMEs) operating in ASEAN countries. To this end, the SMEs are classified into four categories, namely non-innovators and product, process, and product-and-process innovator SMEs. Subsequently, a propensity score weighting (PSW) analysis is performed to adjust for diversity existing across innovative SMEs. The resulting propensity scores are further used to perform the causal effect analysis based on the average treatment effect (ATE) approach, which measures the likelihood of formal finance usage among different types of innovative SMEs. Our ATE results reveal that SMEs simultaneously engaged in product and process innovation show a higher likelihood of using formal finance than non-innovators. However, formal finance usage of SMEs perusing only product/service or process innovation is not any different from non-innovators. Furthermore, our pairwise analysis shows that product and process innovators also exhibit a higher likelihood of formal finance usage than product/service or process innovators. Besides, younger and medium-size product and process innovating SMEs are more likely to use formal finance. These results are robust for different subsamples and firm- and country-level controls.
Keywords: 330; innovation; ASEAN countries; formal finance; propensity score weighting; small and medium enterprises (SMEs)